Energy and fuel efficient parallel mild hybrids for urban roads. (1st August 2016) - Babu, Ajay; Ashok, S.
Graphical abstract: Highlights: Energy and fuel savings depend on battery charge variations and the vehicle speed parameters. Indian urban conditions provide lot of scope for energy and fuel savings in mild hybrids. Energy saving strategy has lower payback periods than the fuel saving one in mild hybrids. Sensitivity to parameter variations is the least for energy saving strategy in a mild hybrid. Abstract: Fuel economy improvements and battery energy savings can promote the adoption of parallel mild hybrids for urban driving conditions. The aim of this study is to establish these benefits through two operating modes: an energy saving mode and a fuel saving mode. The performances of a typical parallel mild hybrid using these modes were analysed over urban driving cycles, in the US, Europe, and India, with a particular focus on the Indian urban conditions. The energy pack available from the proposed energy-saving operating mode, in addition to the energy already available from the conventional mode, was observed to be the highest for the representative urban driving cycle of the US. The extra energy pack available was found to be approximately 21.9 times that available from the conventional mode. By employing the proposed fuel saving operating mode, the fuel economy improvement achievable in New York City was observed to be approximately 22.69% of the fuel economy with the conventional strategy. The energy saving strategy was found to possess the lowest payback periods and highest immunity to variations in various cost parameters.